2021
DOI: 10.3389/fmed.2021.644678
|View full text |Cite
|
Sign up to set email alerts
|

Human-Based Advanced in vitro Approaches to Investigate Lung Fibrosis and Pulmonary Effects of COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has caused considerable socio-economic burden, which fueled the development of treatment strategies and vaccines at an unprecedented speed. However, our knowledge on disease recovery is sparse and concerns about long-term pulmonary impairments are increasing. Causing a broad spectrum of symptoms, COVID-19 can manifest as acute respiratory distress syndrome (ARDS) in the most severely affected patients. Notably, pulmonary infection with Severe Acute Respiratory S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 276 publications
0
28
0
Order By: Relevance
“…Micro-injuries to the alveolar epithelium can result in abnormal wound healing response, and potentially, to lung fibrosis [ 55 ]. The cuboidal alveolar epithelial cells type II that produce pulmonary surfactant proteins, are critically involved in the return to homeostasis, orchestrating the resolution of inflammation and initiating tissue repair [ 2 , 27 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Micro-injuries to the alveolar epithelium can result in abnormal wound healing response, and potentially, to lung fibrosis [ 55 ]. The cuboidal alveolar epithelial cells type II that produce pulmonary surfactant proteins, are critically involved in the return to homeostasis, orchestrating the resolution of inflammation and initiating tissue repair [ 2 , 27 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our study revealed that the Jak-STAT signaling pathway 19 , Cytokine-Cytokine receptor interactions 20 , MAPK signaling pathway 21 , Lung Fibrosis [22][23][24] , Chemokine signaling pathway 22 , Toll-like receptor signaling are the major pathways that were represented by identi ed DEGs and GO analysis. These pathways are well known and reported previously to play a crucial role in SARS-CoV-2 associated pathophysiology (Fig.…”
Section: Identi Cation Of Degsmentioning
confidence: 83%
“…Fibroblast had almost been studied in the fibrotic remodeling and persistent reduced oxygenation in some patients followed by ARDS. Uncontrolled fibroblast proliferation and the deposition of collagen and extracellular matrix (ECM) proteins were involved in this process (Kiener et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%